'Something On Women For the Crime Bill': The Construction and Passage of the Violence Against Women Act, 1990-1994 - Meisel, Irene (2016)
'Something On Women For the Crime Bill': The Construction and Passage of the Violence Against Women Act, 1990-1994 By Irene Meisel Advisor: Professor Sandi E. Cooper 'Something on Women for the Crime Bill' examines the legislative and theoretical history of the Violence Against Women Act (VAWA), signed into law in 1994. It explores the deeply intertwined relationship between the tough-on-crime and feminist movements that shaped both the bill itself and the political discussion surrounding it. The bill inherited a host of ideas about crime, criminality, and race from the 1968 Omnibus Crime Control and Safe Streets Act, leading to a very particular representation of the rapist as a black criminal inhabiting the streets. It merged the categories of rape and domestic violence into one classification of 'violence against women,' eliminating the need to address the particular characteristics of either and resulting in even greater erosion of the feminist anti-rape message. This dissertation also details the role of the NOW Legal Defense and Education Fund (NOW LDEF) in the bill's crafting and passage. NOW LDEF's participation in VAWA's creation represented a political coming of age for second-wave feminism, but the organization's eagerness to pass a civil rights remedy for addressing rape caused its staff to view the very damaging effects of the bill's other provisions as mere collateral. Finally, 'Something on Women for the Crime Bill' describes the hitherto undocumented efforts of a number of the American Civil Liberties Union, the NAACP, and the Leadership Conference on Civil Rights, all of which warned against VAWA's destructive measures, to worked behind the scenes to halt its passage, and or to ameliorate its effects